Conceptual approaches to green economy of Belarusian regions - Palonik, Stiapan S.; Smaliarova, Maryna A. (Journal of the Belarusian State University. Economics, 2018)
In the scientific article it is developed a methodical approach for evaluating the competitiveness of regions of the Republic of Belarus taking into account economic, environmental and social components, including two main directions. The first one is the construction of the system of indicators: economic, environmental, social. The second area involves the calculation of group indices of economic, environmental and social components with following determination of the integral index, which gives an indication of the level of sustainability of socio-economic development of the region. It is used chain indices as the tempo characteristics of three components of competitiveness for the period from 2010 till 2015. It is developed the final integrated rate of competitiveness of regions of the Republic of Belarus for the period from 2010 till 2015. It is offered the measures, the implementation of which involves the use of innovative technologies and sustainable approach to the use of its own resources for the transition to the principles of green economy. It allow consider the environmental factor in the production of clean food products, improve the quality of life of the population of the Republic of Belarus.
Keywords: the competitiveness of the region; economic, environmental and social indices of the development of the region; sustainable socio-economic development of the region; stimulation of economic development of the region; the effectiveness of the strategy of economic policy of the region